El mito de Sīyāvuš y las leyendas actuales de Bujará - Mohammadi Shirmahaleh, Shekoufeh (El Colegio de México, 2019)
The myth of Sīyāvuš is one of the oldest and most important in the Iranian world and many rituals are related to it. Sīyāvuš is a deity of plants whose death and annual resurrection guarantees nature’s rebirth after cold seasons. To this day, it remains a powerful influence in Iran and Central Asia thanks to the legends that have sprung up from it. This paper describes some of these legends, collected during a fieldwork trip in 2018, and reinterprets them in reference to this myth.